Cooperation south - United Nations Development Programme (New York, N.Y. : The Programme, 2001)
"The magazine of technical co-operation among developing countries, TCDC."
Title from cover.
The logo of TCDC form the two o's in the title.
Year and number designation dropped with 1991, no. 1.
Issues for Sept. 1994 and May 1995 called: Special issue; Oct. 1995: UN 50th anniversary issue.
Three issues in 1991, 2 each in 1992-1993, 1 in 1994, 2 in 1995, and 1 in 1996.